EFFECT OF CLINICAL PHARMACIST MEDIATED COUNSELLING IN HYPERTENSIVE PATIENTS ON HEALTH RELATED QUALITY OF LIFE (World Journal of Current Medical and Pharmaceutical Research, 2020)
Background: Hypertension has become a significant problem in developing countries. The management of hypertension involves long term treatment & life style modification which will have greater impact on HRQoL. This study aims to give patient counseling regarding risk factors, life style modifications, pharmacological therapy & medication adherence in hypertension which in turn improves HRQoL.Aim and objectives: To assess the effect of clinical pharmacist mediated counselling in hypertensive patients on health related quality of life.  Specific objectives: To assess the disease related knowledge of hypertensive patients, To assess the medication adherence of hypertensive patients,To design suitable patient information leaflet (PIL) on hypertension and its management use the same to educate the patients,To assess the effect of education on outcome of treatment (blood pressure level) and quality of life of these patients.Methodology: Prospective observational study. The study was conducted in Jayabharath hospital, Nellore. which was conducted for a period of 6 months from June 2019- November-2019.Hypertensive patients, of either sex, above 18 years of age, with or without co-morbidities and Patient willing to give there informed consent to participate in the study are included in our study and the Pregnant hypertensive patients are excluded from the study.Results and Discussion: At baseline there was no significant difference between the blood pressures, QoL score, adherence score, and KAP of the test and control groups. As patient in both group continued to see there physician regularly, both showed in improvement in blood pressure control at final follow up. However improvement in the test group blood pressure was more significant reduction (p